A Correlation Between the Severity of Sleep-Disordered Breathing and the Frequency and Duration of Bradyarrhythmias in Patients with Cardiovascular Risk Factors: A Systematic Review - Putri Rahmi Maharani; Robby Rachman; Kevin Habib Alhuda (International Medical Journal Corp. Ltd, 2025)
INTRODUCTION : Sleep-disordered breathing (SDB) is a highly prevalent condition strongly associated with cardiovascular morbidity. While its link to tachyarrhythmias is well-established, the relationship with bradyarrhythmias is less synthesized. This systematic review aims to evaluate the correlation between SDB severity and the frequency and duration of bradyarrhythmias in patients with cardiovascular risk factors. METHODS : A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for observational studies and clinical trials investigating the association between SDB severity and bradyarrhythmic events in adults with cardiovascular risk factors. Study selection, data extraction, and risk of bias assessment using the ROBINS-I tool were performed independently by two reviewers, adhering to PRISMA 2020 guidelines. Outcomes of interest included the incidence, frequency, and duration of sinus bradycardia, sinus pauses/arrest, and atrioventricular (AV) block, as well as mean/minimum nocturnal heart rate and adjusted risk estimates. RESULTS : The evidence consistently demonstrates a high comorbid disease burden, with a pooled prevalence of nocturnal bradycardia in patients with obstructive sleep apnea (OSA) of approximately 69.8% and a pooled prevalence of OSA in patients with bradycardia of 56.8%. A significant dose-response relationship was identified, with increasing SDB severity, measured by the Apnea-Hypopnea Index (AHI) or Oxygen Desaturation Index (ODI), correlating with a higher frequency and duration of bradyarrhythmic events. Patients with severe SDB had significantly higher odds of experiencing sinus pauses greater than 3 seconds (OR, 10.26; 95% CI, 2.18–48.40) and sinus bradycardia below 40 bpm (OR, 3.00; 95% CI, 1.36–6.60) compared to those with no or mild SDB. The highest prevalence and severity of SDB were observed in patients paced for high-degree AV block. DISCUSSION : The synthesized evidence supports a strong, dose-dependent relationship between SDB severity and the burden of nocturnal bradyarrhythmias. This association is primarily driven by intermittent hypoxia-induced vagal hyperactivity. The high prevalence of undiagnosed SDB in patients receiving pacemakers suggests that SDB may be a significant, reversible cause of bradyarrhythmias, potentially leading to avoidable implantations. Discrepancies between community-based and clinic-based cohort studies suggest that the arrhythmogenic risk of SDB is magnified in patients with a higher burden of underlying cardiovascular disease. CONCLUSION : The severity of SDB is a significant predictor of the frequency and duration of nocturnal bradyarrhythmias in patients with cardiovascular risk factors. Systematic screening for SDB is warranted in patients presenting with significant nocturnal bradycardia or AV block to identify a modifiable cause and potentially alter therapeutic management, including the need for permanent pacing.